All care bundles are equal, but some are more equal than others - Mulder, Tessa; Kluytmans, Jan (Annals of Laparoscopic and Endoscopic Surgery; Vol 2 (September 2017): Annals of Laparoscopic and Endoscopic Surgery, 2017)
Surgical site infections (SSIs) are one of the most common hospital-acquired infections in surgical patients (1).